Interventions and assessment tools addressing key concepts people need to know to appraise claims about treatment effects: a systematic mapping review. Issue 1 (December 2016) - Austvoll-Dahlgren, Astrid; Nsangi, Allen; Semakula, Daniel
Abstract Background People's ability to appraise claims about treatment effects is crucial for informed decision-making. Our objective was to systematically map this area of research in order to (a) provide an overview of interventions targeting key concepts that people need to understand to assess treatment claims and (b) to identify assessment tools used to evaluate people's understanding of these concepts. The findings of this review provide a starting point for decisions about which key concepts to address when developing new interventions, and which assessment tools should be considered. Methods We conducted a systematic mapping review of interventions and assessment tools addressing key concepts important for people to be able to assess treatment claims. A systematic literature search was done by a reserach librarian in relevant databases. Judgement about inclusion of studies and data collection was done by at least two researchers. We included all quantitative study designs targeting one or more of the key concepts, and targeting patients, healthy members of the public, and health professionals. The studies were divided into four categories: risk communication and decision aids, evidence-based medicine and critical appraisal, understanding of controlled trials, and science education. Findings were summarised descriptively. Results We included 415 studies, of which the interventions and assessment tools we identified included only a handful of the key concepts. The most common key concepts in interventions were "Treatments usually have beneficial and harmful effects, " "Treatment comparisons should be fair, " "Compare like with like, " and "Single studies can be misleading." A variety of assessment tools were identified, but only four assessment tools included 10 or more key concepts. Conclusions There is great potential for developing learning and assessment tools targeting key concepts that people need to understand to assess claims about treatment effects. There is currently no instrument covering assessment of all these key concepts.